Analysis of Industrial Practice Activities In Vocational Schools In Facing Industrial Revolution 4.0 - Safitri, Endriana Retno; Nurlaela, Lutfiyah; Rijanto, Tri; Munoto, Munoto (International Journal for Educational and Vocational Studies, 2020)
Industry 4.0 is the state of the industry in the face of the 21st century when there is a massive change through technology that opens a barrier between the digital and physical worlds. There will be many types of jobs lost, and new types of jobs will emerge. Faced with this, high mastery skills are required by graduates. In vocational high schools the mastery of skills is done by sending students directly into industrial work practices. But are IWP activities really able to be used to improve skills in dealing with Industry 4.0? What types of skills students must master when dealing with industry 4.0 This article will conduct a study of various related literature about IWP and industry 4.0. The results of the study will link the effects resulting from IWP activities and needs in industry 4.0. The results of the study indicate that the IWP program in vocational high schools needs some improvement to be able to produce vocational high school graduates who are ready to face industry 4.0.